Penerapan Hukum Terhadap Tindak Pidana Penyalahgunaan Narkotika Golongan I Menurut Studi Kriminologi (Di BNNP Bengkulu) (Fakultas Hukum Dehasen, 2019)
Narcotics are substances or drugs derived from plants or non-plants, both synthesis and semisentesis, which can cause a decrease or change in consciousness, loss of taste, reduce pain relief, and can lead to dependence, which are differentiated into groups as attached in Law Number 35 of 2009 concerning Narcotics. Abuse is people who use narcotics without rights or against the Law. The Bengkulu Province National Narcotics Agency is a vertical Government Institution that is located under and responsible to the National Narcotics Agency which is an institution that aims to carry out the Drug Prevention and Illicit Circulation Program (P4GN) with various activities through the field of Prevention and Community Empowerment. behind, then the problem in this research is the application of law in handling the misuse of criminal acts of class I narcotics at the BNNP Bengkulu. Preventive Theory. Theory of crime is a number of theories about the causes of crime. This type of research is empirical research. criminal Narcotics abuse class I in the Bengkulu Province National Narcotics Agency. Drug Abuse and Illicit Circulation (P4GN) with various activities through the field of prevention and community empowerment in the area of Rehabilitation and Field Implementation of strategic plans and work plans in the areas of conflict and eradication and illicit circulation of social, psychotropic, precursor and addictive ingredients in addition to addictive ingredients for tobacco and alcohol which was later called P4GN in Bengkulu Province. Implementation of technical policies in the field of community empowerment, rehabilitation and eradication in the Bengkulu Province. Implementation of technical guidance and supervision of P4GN for BNNK / City in Bengkulu Province. Factors Affecting Drug Abuse Individual Factors, Environmental Factors, Drug Willing Factors. Keywords: legal and Preventive application